International Accounting and Reporting Issues - 2003 Review - United Nations Conference on Trade; Development (United Nations, 2004)
This volume of the Review contains the proceedings of the twentieth anniversary session of the Intergovernmental Working Group of Experts on International Standards of Accounting and Reporting (ISAR). The session deliberated on corporate governance disclosure requirements, reporting on the impact of corporations on society, and a revised model curriculum for professional accountants.